Eksistensi Civic Engagement dan Elite Integration dalam Konflik Sunni-Syiah di Sampang - Mujahidah, Affaf (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2015)
The conflict between Sunni and Shia groups in Sampang did not take place at once but rather through certain periods of time when each conflict had triggered another conflict. In each period, either the government and religious elite has a pivotal role to evaluate, charge or discharge, civic engagement and elite integration in the conflict process. This article is aimed to analyze the violence against Shia group in three periods of time: pre-conflict, midi-conflict, and post-conflict. The first period started after Kiai Makmun had passed away. The second was when the violence occurred in December 29th 2011 and August 26th 2012. And the third occurred after the violence had taken place. Although the conflict has run for several years, it has not shown the end. In order to explain this problem, this article bases on two hypotheses: first, the conflict has been caused by the absence of civic engagement. And second, which was caused the conflict continuation, has been caused by elite integration, which has never occurred on the society. This article concludes two things: first, civic engagement that can find only intra-communal engagement (intra-community engagement). And second, elite integration cannot be created because Shia’s Kiai had not been legitimized by Sunni’s Kiai.